2012
DOI: 10.4149/av_2011_04_311
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rta protein of Epstein-Barr virus on the cell cycle in HeLa cells

Abstract: Summary. -Epstein-Barr virus (EBV) replication and transcription activator (Rta) is an immediate-early transcription factor that mediates the switch from latent to lytic infection. DNA viruses often modulate the function of critical cell cycle proteins to maximize the efficiency of virus replication. Here we have examined the effect of Rta on cell cycle progression. Cell cycle analysis revealed that Rta induced HeLa cells in G0/G1-phase to reenter the S-phase. Analysis of the expression pattern of a key set of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…EBV is also known to cause genomic instability which can occur when EBV switches between its lytic and latent phases. These phases are heavily influenced by the BZLF1 gene which arrests cell cycle development, and the BRLF1 gene which can cause the cell to inappropriately reenter the S phase causing problems in chromosomal segregation [13,14]. EBV, like many cancer-causing agents, has in-built mechanisms to evade the immune system which stymies the physiological response to anti-tumorigenesis.…”
Section: Epstein-barr Virus and Nasopharyngeal Carcinomamentioning
confidence: 99%
“…EBV is also known to cause genomic instability which can occur when EBV switches between its lytic and latent phases. These phases are heavily influenced by the BZLF1 gene which arrests cell cycle development, and the BRLF1 gene which can cause the cell to inappropriately reenter the S phase causing problems in chromosomal segregation [13,14]. EBV, like many cancer-causing agents, has in-built mechanisms to evade the immune system which stymies the physiological response to anti-tumorigenesis.…”
Section: Epstein-barr Virus and Nasopharyngeal Carcinomamentioning
confidence: 99%
“…It was reported that the EBV lytic protein BZLF1 arrested cells in G0/G1 [ 27 ], G1/S [ 28 ] and G2/M [ 29 ]. It has been reported that BRLF1-expressing cells reenters S phase [ 30 ]. Our previous studies demonstrated that BRLF1 has ability to interfere with cells at the G1/S transition and induces a cellular senescence [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%